THE SEXUAL VIOLENCE AGAINST WOMEN (CIPEEX, 2022)
THE PRESENT WORK INVESTIGATES THE LEGAL TREATMENT IN BRAZIL OF VIOLENCE AGAINST WOMEN IN THE DOMESTIC SPHERE. THE CONCEPTS AND VARIATIONS OF VIOLENCE AGAINST WOMEN REPRESENTED BY THE PENAL CODE AND THE MARIA DA PENHA LAW ARE HIGHLIGHTED, AS WELL AS OTHER TERMS RELATED TO THE UNDERSTANDING OF THEMES SUCH AS GENDER AND PATRIARCHY GENDER VIOLENCE IS NOT LIMITED TO AGGRESSION THAT A MAN COMMITS AGAINST A WOMAN, BUT IN EVERY WAY ABOUT CRIMES SUPPORTED BY THE NORMATIVE STANDARDS OF SOCIETY, ABOUT WHAT SHOULD BE A MAN AND WHAT IT IS TO BE A WOMAN. THE MAIN OBJECTIVE IS TO PRESENT A THEORETICAL CONTEXT ON SEXUAL VIOLENCE AGAINST WOMEN, TO CLARIFY THE MAIN CHANGES THAT HAVE OCCURRED OVER THE YEARS IN THE LEGISLATION AND CULTURE OF OUR COUNTRY. THE TOOLS USED WERE REVIEWS OF BIBLIOGRAPHIC RESEARCH, IN REFERENCE MATERIALS IN THE AREA, INCLUDING BOOKS, ARTICLES AND LEGISLATIVE REFERENCES, WHICH ARE AVAILABLE IN PRINTED AND ONLINE VERSIONS. IT WAS GATHERED AND COMPARED THE DIFFERENT DATA FOUND IN THE SOURCES AND LISTED THE MAIN EVENTS ABOUT THE LEGAL APPROACH TO SEXUAL VIOLENCE, MAKING IT POSSIBLE TO KNOW MORE DEEPLY THE SUBJECT AND ITS PENALIZATION IN BRAZILIAN LEGISLATION.
Keywords: sexual violence; Maria da Penha Law; Genre.